Can Arctic Sea Ice Melting Lead to More Summertime Heat Extremes? - Wu, Yutian; Sun, Lantao; Terry, Owen (Geophysical research letters, 2025)
We quantify the impact of late 21st century Arctic sea ice loss on Northern Hemisphere (NH) summertime heat extremes using model simulations that are forced by the future Arctic sea ice loss. First, we find an overall increase of heat extreme frequency in the NH continents in our model simulations, but only in the presence of ocean‐atmosphere coupling. The increased frequency of heat extremes is entirely due to mean temperature increase. However, in comparison to the corresponding future warming scenario, in general, increases in heat extremes in NH continents due to the future Arctic sea ice loss are relatively small. The results suggest a non‐negligible but limited role of the future Arctic sea ice loss on contributing to the NH summertime heat extremes. Plain Language Summary The role of the changing Arctic on the rest of the globe, especially on weather extremes, is a subject of interest. Using climate model simulations that isolate the role of future Arctic sea ice loss, we show an overall increase of heat extreme frequency in the northern hemisphere (NH) land regions as a result, but only in the presence of a changing ocean circulation and ocean‐atmosphere coupling. However, the contribution of future Arctic sea ice loss to the NH heat extremes is relatively small, compared to the radiative forcing of anthropogenic greenhouse gases in general. Key Points The late 21st century Arctic sea ice loss can lead to more summertime heat extremes but only in the presence of ocean coupling The increased frequency of heat extremes is entirely due to mean temperature increase The role of future Arctic sea ice loss on northern hemisphere land heat extremes is relatively small compared to its corresponding future projection